DEVELOPING STUDENTS’ WRITING PERFORMANCE THROUGH PEER FEEDBACK WITH CHAT SYSTEM - Nanik Sri Rahayu (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
To English learners, writing has been considered the most difficult skill for some reasons such as the grammar, the vocabulary, and the background knowledge. To help them develop their writing skill, it is recommended to employ the peer feedback in the teaching learning process at the writing class. Providing feedback in the process of writing tend to have beneficial help for the students to improve the quality of their work, especially in writing an essay. This expectation is generally agreed since students often face difficulties in accomplishing their writing due to the complexity of the writing itself, the students’ factors and the teacher’s factors. From the writing aspect, mastering the language form such as grammar, diction, etc and the content of the essay seems to be common problems for many EFL students.